Evaluasi Peran Masyarakat Dalam Pengelolaan Sampah di Desa Wisata Apung Kampung Malahing Kota Bontang - Zukhriadi, Ricky Renaldi Eka Taruna Zukhriadi; Komariyah , Laili; Sandy, Aisyah Trees (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
Community participation in waste management is an important aspect in creating a clean and healthy environment by evaluating several aspects. This study aims to determine waste management and the constraints faced by the community's role in managing waste on the sea which is reviewed from legal and regulatory aspects. institutional, operational, financing, and the role of the community in managing waste. This research is a qualitative descriptive study, using observation, interview, and documentation techniques as data collection techniques. Determination of research subjects using purposive sampling. The results show that there are no legal aspects that apply, financing aspects, institutional aspects and operational aspects have been carried out quite well, but in the aspect of community roles it is still not implemented well enough because of several obstacles related to work and education level. Evaluation using the Miles and Humberman Analysis Technique occurs grouping in every aspect. Suggestions for the people of Malahing Village to be more concerned about their environment, take part in managing waste, and be able to innovate, training on managing household waste into compost, and so on.